The Effect of Demonstration in Preparing a Nutritious Food Menu on Nutrition Consumption Patterns of Pregnant Women - Dewi Sri Sumardilah; Mindo Lupiana; Aprina Aprina (Universitas Aisyah Pringsewu, 2021)
Stunting in children has started since before birthing due to poor nutritional conditions of the mother during pregnancy. The nutrients that pregnant women need to maintain the health of their fetuses are protein, folic acid, calcium, vitamin A, vitamin D, and iron. The practice of consuming nutritious food is strongly influenced by the level of knowledge and behavior towards food. Lack of knowledge about nutrition can cause pregnant women to be unable to design and arrange nutritious meals that must be consumed. This research design is a quasi-experimental approach with a nonrandomized pretest-posttest control group design approach. The illustrations used are 50 pregnant women and will be divided into one control group and one treatment group. As the independent variable is the practice of compiling a nutritious meal menu, the dependent variable is the pattern of consuming nutrients, and the confounding variable is the age of the pregnant woman, the level of learning of the pregnant woman, the level of family income, and the gestational age. The information analysis used an independent t-test and a dependent t-test. The results of the research show that there is an increase in the average consumption of protein, Fe, folic acid, and zinc after being given treatment in the form of the practice of compiling a nutritious menu for pregnant women. After that, there is a significant comparison between the average nutritional consumption before and after being given leaflets and the practice of compiling menus. Next, there is a significant comparison between the average consumption of protein and zinc between the two groups and there is no significant comparison between the average consumption of Fe and Folic acid in both groups. The advice given is to increase knowledge, behavior, and expertise about nutritious food for pregnant women. So that demonstration procedures or practices need to collaborate with other counselling methods and to increase family income for pregnant women, it is necessary to raise family businesses carried out by pregnant women through the efforts to increase prosperous family income Program.Abstrak: Stunting pada anak telah diawali semenjak saat sebelum kelahiran yang diakibatkan sebab kondisi gizi ibu yang kurang baik sepanjang kehamilan. Zat gizi yang sangat diperlukan ibu hamil buat melindungi kesehatan janinnya merupakan protein, asam folat, kalsium, vit A, vit D, serta zat besi. Konsumsi santapan bergizi sangat dipengaruhi oleh tingkatan pengetahuan serta perilakunya terhadap santapan. Pengetahuan yang kurang tentang gizi dapat menimbulkan ibu hamil tidak sanggup merancang serta menyusun santapan bergizi yang wajib dikonsumsinya. Rancangan riset ini merupakan quasi experiment dengan pendekatan nonrandomized pretest posttest control group design. Ilustrasi yang digunakan berjumlah 50 orang ibu hamil serta hendak dipecah jadi 1 kelompok kontrol serta 1 kelompok perlakuan. Variable independen merupakan praktek menyusun menu santapan bergizi, variable dependen merupakan pola mengkonsumsi zat gizi, serta variable pengganggu merupakan usia ibu hamil, tingkatan pembelajaran ibu hamil, tingkatan pemasukan keluarga, serta umur kehamilan. Analisa informasi memakai uji independen t test serta dependent t test. Hasil riset menampilkan terdapat kenaikan rata- rata mengkonsumsi protein, Fe, asam folat, serta zinc sehabis diberikan perlakuan berbentuk praktek menyusun menu bergizi ibu hamil. Setelah itu terdapat perbandingan yang bermakna antara rata- rata mengkonsumsi gizi saat sebelum dengan setelah diberikan leaflet serta praktek menyusun menu. Berikutnya terdapat perbandingan yang bermakna antara rata- rata mengkonsumsi protein serta zinc antara kedua kelompok serta tidak terdapat perbandingan bermakna antara rata- rata mengkonsumsi Fe serta Asam folat pada kedua kelompok Saran yang diberikan merupakan buat tingkatkan pengetahuan, perilaku, serta keahlian tentang santapan bergizi ibu hamil hingga tata cara demonstrasi ataupun praktek perlu dikolaborasikan dengan tata cara penyuluhan yang lain, serta buat tingkatkan pemasukan keluarga ibu hamil butuh dibesarkan usaha keluarga yang dilakukan oleh ibu hamil lewat program UPPKS (Usaha Kenaikan Pemasukan Keluarga Sejahtera)